Model Pembelajaran BIPA untuk Menguatkan Identitas Budaya dan Nasionalisme bagi Anak Diaspora - Ardhana Reswari Diyah Putri (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The teaching of Indonesian as a Foreign Language (IFL) could be a tools in cultural diplomacy and a means of preserving national identity, while also possessing broader potential, not merely to introduce Indonesian to foreign speakers, but to restore a sense of ‘home’ in Indonesia for those with ancestral ties to the nation. This paper adopts a futurological perspective in language education to design an inclusive, adaptive, and culturally grounded model of BIPA, with a particular focus on reconnecting children of Indonesian descent abroad with the language and culture of their heritage. The paper evaluates the limitations of conventional BIPA approaches and proposes a hybrid model that integrates technology, personalization, and cultural activities to foster both nationalism and functional language skills. In the context of diaspora learners, collaboration among various stakeholders plays a crucial role in BIPA instruction, particularly in reintroducing Indonesian cultural values into the lives of these children.